Women's assault on male university degrees; change and continuity in gender discrimination (Praxis Educativa, 2012)
At the beginning of the XX century, female students at universities were absolute minority; at the end of the century they already constituted an overwhelmingly majority in almost all Western Universities. Should we celebrate the end of any sexist discrimination in tertiary education? Enrolment according to disciplinary orientation shows disparities disguised under the overall figure. Two out three students at the public Uruguayan University are women; this has not prevented the persistence of a historic differentiation between “masculine” and “female” disciplines. But it is clear that things changed, and everything suggests an irreversible feminization process of all careers in universities. We will here examine the trends revealed by enrolment figures over the three decades separating the 1974 and 2007 censuses.
Keywords: university; feminization; “masculine” and “female” disciplines